Cell Behavior of Primary Fibroblasts and Osteoblasts on Plasma-Treated Fluorinated Polymer Coated with Honeycomb Polystyrene - Fajstavrová, Klára; Rimpelová, Silvie; Fajstavr, Dominik; Švorčík, Václav; Slepička, Petr (Materials (Basel, Switzerland), 2021)
The development of new biocompatible polymer substrates is still of interest to many research teams. We aimed to combine a plasma treatment of fluorinated ethylene propylene (FEP) substrate with a technique of improved phase separation. Plasma exposure served for substrate activation and modification of surface properties, such as roughness, chemistry, and wettability. The treated FEP substrate was applied for the growth of a honeycomb-like pattern from polystyrene solution. The properties of the pattern strongly depended on the primary plasma exposure of the FEP substrate. The physico-chemical properties such as changes of the surface chemistry, wettability, and morphology of the prepared pattern were determined. The cell response of primary fibroblasts and osteoblasts was studied on a honeycomb pattern. The prepared honeycomb-like pattern from polystyrene showed an increase in cell viability and a positive effect on cell adhesion and proliferation for both primary fibroblasts and osteoblasts.
Keywords: fluorinated ethylene propylene; cell viability; plasma treatment; honeycomb-like pattern; polystyrene; cytocompatibility